THE SPEKL-VIsUALIZATion METHOD IN THE MICROCIRCULATION RESEARCH - S. N. Tabunov; T. V. Hardzeichuk; M. H. Tkhostov; P. N. Nikitenko; K. N. Runkevich; I. V. Kishkevich; E. S. Kashitskii (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
In this operation results of the application developed by authors hardware and the software of dynamic measurement of biospeckles for monitoring of microcirculation of the person when holding physiotherapeutic procedures are provided.